Women’s Civil Rights and their Protection Mechanisms in International and National Legislation - Boukhalfa, Abdelkrim (Journal of Legal Studies and Researches, 2021)
The civil rights of women has gained great interest at the national and international levels. At the national level devoted to various legislation of constitutions and legal texts of civil rights for women. On the international level, the United Nations and the various actors in the field of human rights bodies have signed international conventions on the rights of others. In particular, the right to life, security and physical integrity of women, the right to equality between the sexes, without any discrimination, and given legal protection against any violation by devoting the international mechanisms to protect it by organs of the United Nations body.